What Factors Contribute to the Inconsistent Use of Insecticide Treated Bed Nets in Tropical Africa? A Review of the literature on Malaria Prevention - Alan Ibeagha; Robert A.C. Ruiter; Nicole H.T.M. Dukers- Muijrers; Christian J.P.A. Hoebe (International Journal of Psychology and Health Science, 2025)
Objective: To review the evidence showing the factors associated with inconsistent use of insecticide-treated bed nets (ITN), primarily among pregnant women and households in tropical Africa.  Methods: Literature from the last 11 years was reviewed to identify reasons for inconsistent insecticide-treated bed net use. The review primarily focused on empirical studies covering issues related to pregnant women and households in tropical Africa. The reasons for inconsistent use of ITN were broadly classified as personal and external factors as guided by the socio-ecological model. Results: Personal factors identified include psychosocial barriers, socio-economic barriers, and biological barriers. Within the psychosocial barriers, issues relating to outcome expectations, acceptance, risk perception, misconceptions about malaria etiology, local terminologies, and self-treatment were reported. Income status was the primary focus of the socio-economic barriers, while, breathing difficulty, unfriendly smells and discomforts from reactions to the ITN made up the biological factors. External factors were identified at the interpersonal, organizational, community, and environmental levels. Key themes identified under each level respectively include gender-based issues (Interpersonal), healthcare system (organizational), agency/community practices (community), and heat (environmental). Conclusion: The review revealed barriers to consistent ITN use among pregnant women and households in tropical Africa. Some key barriers to consistent ITN use, identified, include wrong beliefs, misconceptions about malaria etiology, risk perception, weak or no acceptance of the ITN and gender-based issues. To tackle this challenge, in-depth behavior research based on the appropriate use of behavior theories would be needed. This would help to unpack why and how these factors affect insecticide treated net use behavior. The findings from the behavior change research can then be used to design and implement an effective behavior change intervention that would reduce malaria related morbidity and mortality among the target population.